A Study of English-Speaking Skill of Third - Year Students Through Communicative Approach by Using Games - KEOPHASITH, Vatsana; PHOMMANITH, Khamsone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research applying One-shot Case Study aimed 1) to examine the third - year students speaking skill provided by Communicative Approach using games, and 2) to investigate the student’s satisfaction towards Communicative Approach using games. The target group of this study was the third - year students who are taking chemistry course in the second semester, academic year 2019-2020 at Faculty of Education with a total number of 22 by Cluster Random Sampling. The research instruments were 6 Communicative Approach Lesson Plans, for 12 hours. Moreover, the instruments used for data collection were speaking test, and questionnaire. The descriptive statistics for analyzing the data included the frequency, percentage, mean and standard deviation. The findings were follows: 1) The students gained the scores of Communicative Approach using games passing defined criteria of 70 percent, accounted for 73.19. A number of the students who passed the criteria were 81.48 percent, which was higher than the defined criteria. 2) Overall, the students’ satisfaction towards Communicative Approach using games was at the highest level ( = 4.74, S.D. = 0.42).